Heat response testing in elite rugby sevens athletes: An eye to Tokyo 2020 - Fenemor, S.; Gill, N.; Sella, F.; Beaven, C. M.; Driller, M. (Sport and Exercise Science New Zealand Conference, 2018, 2018)
Little is known about the physiological and perceptual responses of elite rugby sevens athletes to the heat stress expected at the 2020 Tokyo Olympics. Methods: Seven elite male rugby sevens athletes completed a heat response test (HRT) consisting of a 15-min warm up, simulated sevens game and 1.2 km time trial (TT) on a treadmill in ambient (AMB; 20 °C, 50% rH) and Tokyo (HOT; 35 °C, 80% rH) conditions. Tympanic temperature (TTymp), heart rate (HR), rate of perceived exertion (RPE), thermal sensation (TS), thermal comfort (TC) and thirst were measured at baseline, half time, and pre-TT. Results: TTymp and HR during HOT were significantly greater at half-time (1.4 ± 0.7 °C; 19 ± 15 bpm) and pre-TT (1.6 ± 0.7 °C; 25 ± 16 bpm) compared to AMB (all mean ± 95% CI; p<0.05). TTymp and HR were not different at baseline. TS, TC and RPE during HOT were greater at all timepoints (all ES > 1.2), whereas thirst was only greater pre-TT (ES = 1.2). Mean (± SD) time to complete the TT was greater in HOT (5.58 ± 0.83 min) compared to AMB (4.43 ± 0.27 min; ES = 1.8). Take Home Message: Simulated environmental conditions expected during the 2020 Tokyo Olympics can impact physiological, perceptual and performance markers during a rugby sevens specific HRT.